Do Central Banks Respond to Exchange Rate Movements? a Markov-Switching Structural Investigation - Ragna Alstadheim; Hilde C. Bjørnland; Junior Maih (Norges Bank, 2013)
Do central banks respond to exchange rate movements? According to Lubik and Schorfheide (2007) who estimate structural general equilibrium models with monetary policy rules, the answer is "Yes, some do". However, their analysis is based on a sample with multiple regime changes, which may bias the results. We revisit their original question using a Markov switching set up which explicitly allows for parameter changes. Fitting the data from four small open economies to the model, we find that the size of policy responses, and the volatility of structural shocks, have not stayed constant during the sample period (1982-2011). In particular, central banks in Sweden and the UK switched from a high response to the exchange rate in the 1980s and early 1990s, to a low response some time after inflation targeting was implemented. Canada also observed a regime change, but the decline in the exchange rate response was small relative to the increase in the response to inflation and output. Norway, on the other hand, did not observe a shift in the policy response over time, as the central bank has stayed in a regime of high exchange rate response prior and post implementing inflation targeting.
hdl:11250/2496680
Keywords: C68; E52; F41; 330; MSM; Markov switching; monetary policy; exchange rates; inflation targeting; small open economy